Drivers of Individual and Regional Variation in CMS Hierarchical Condition Categories Among Florida Beneficiaries - Jacobs M; Morris E; Haleem Z; Mandato N; Marlow NM; Revere L (Dove Medical Press, 2023)
Molly Jacobs,1 Earl Morris,2 Zuhair Haleem,1 Nicholas Mandato,3 Nicole M Marlow,1 Lee Revere1 1Department of Health Services Research Management and Policy, University of Florida, Gainesville, FL, USA; 2Department of Pharmaceutical Outcomes and Policy, University of Florida, Gainesville, FL, USA; 3Department of Biology, University of Florida, Gainesville, FL, USACorrespondence: Lee Revere, Email frevere@ufl.eduObjective: To explore hierarchical condition categories (HCC) risk score variation among Florida Fee for Service (FFS) Medicare beneficiaries between 2016 and 2018.Data Sources: This study analyzed HCC risk score variation using Medicare claims data for Florida beneficiaries enrolled in Parts A & B between 2016 and 2018.Study Design: The CMS methodology analyzed HCC risk score variation using annual mean county- and beneficiary-level risk score changes. The association between variation and beneficiary characteristics, diagnoses, and geographic location was characterized using mixed-effects negative binomial regression models.Data Collection: Not applicable.Principal Findings: Counties in the Northeast [marginal effect (ME)=− 0.003], Central (ME=− 0.021), and Southwest (ME=− 0.009) Florida have relatively lower mean risk scores. A higher number of lifetime (ME=0.246) and treatable (ME=0.288) conditions were associated with higher county-level risk scores, while more preventable conditions (ME=− 0.249) were associated with lower risk scores. Counties with older beneficiaries (ME=0.015) and more Blacks (ME=0.070) have higher risk scores, while having female beneficiaries reduced risk scores (ME=− 0.005). Individual risk scores did not vary by age (ME=0.000), but Blacks (ME=0.001) had higher rates of variation relative to Whites, while other races had comparatively lower variation (ME=− 0.003). In addition, individuals diagnosed with more lifetime (ME=0.129), treatable (ME=0.235), and preventable (ME=0.001) conditions had higher risk score variation. Most condition-specific indicators showed small associations with risk score changes; however, metastatic cancer/acute leukemia, respirator dependence/tracheostomy, and pressure ulcers of the skin were significantly associated with both types of HCC risk score variation.Conclusion: Results showed demographics, HCC condition classifications (ie, lifetime, preventable, and treatable), and some specific conditions were associated with higher variation in mean county-level and individual risk scores. Results suggest consistent coding and reductions in the prevalence of certain treatable or preventable conditions could reduce the county and individual HCC risk score year-to-year change.Keywords: risk score, hierarchical condition category, HCC, medical coding